The other-race effect in face learning: Using naturalistic images to investigate face ethnicity effects in a learning paradigm. Issue 5 (May 2017) - Hayward, William G.; Favelle, Simone K.; Oxner, Matt; Chu, Ming Hon; Lam, Sze Man
The other-race effect in face identification has been reported in many situations and by many different ethnicities, yet it remains poorly understood. One reason for this lack of clarity may be a limitation in the methodologies that have been used to test it. Experiments typically use an old–new recognition task to demonstrate the existence of the other-race effect, but such tasks are susceptible to different social and perceptual influences, particularly in terms of the extent to which all faces are equally individuated at study. In this paper we report an experiment in which we used a face learning methodology to measure the other-race effect. We obtained naturalistic photographs of Chinese and Caucasian individuals, which allowed us to test the ability of participants to generalize their learning to new ecologically valid exemplars of a face identity. We show a strong own-race advantage in face learning, such that participants required many fewer trials to learn names of own-race individuals than those of other-race individuals and were better able to identify learned own-race individuals in novel naturalistic stimuli. Since our methodology requires individuation of all faces, and generalization over large image changes, our finding of an other-race effect can be attributed to a specific deficit in the sensitivity of perceptual and memory processes to other-race faces.